PENGARUH GAYA KEPEMIMPINAN DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN KERTAS DI JAWA TIMUR - Ratna Agustina; Agus Sunaryo; Dwi Sigita; Risa Muzrifah (MANAJEMEN DEWANTARA, 2025)
This study aims to analyze the influence of leadership style and career development on employee performance with job satisfaction as an intervention variable in a paper company in East Java. This study uses a quantitative approach with data analysis using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method involving 120 respondents. Data were collected through a survey and analyzed to test the relationship between variables: leadership style, career development, job satisfaction, and employee performance. The study's results indicate that leadership style and career development significantly affect employee performance, both directly and indirectly through job satisfaction as a mediating variable. Job satisfaction has been shown to play an important role as a mediator that connects the influence of leadership style and career development on employee performance. These results provide empirical evidence that increasing effective leadership style and structured career development can increase job satisfaction, ultimately improving employee performance. The contribution of this study lies in developing HR management literature by including job satisfaction variables as a mediating factor in the relationship between leadership style, career development, and employee performance. In addition, this study provides contextual insight for paper companies in East Java to design more effective strategies in improving employee performance